Hollow Dodecahedra Graphene Oxide- Cuprous Oxide Nanocomposites With Effective Photocatalytic and Bactericidal Activity - Shan, Zezhi; Yang, Yanrong; Shi, Haoran; Zhu, Jiali; Tan, Xiao; Luan, Yi; Jiang, Zhenqi; Wang, Ping; Qin, Jieling (Frontiers in Chemistry, 2021)
In this study, a kind of graphene oxide-cuprous oxide (GO-Cu2O) nanocomposites was fabricated with different morphologies to serve as a photocatalytic material for the degradation of organic/inorganic dyes under visible light and the bactericidal effect against pathogenic bacteria. The GO-Cu2O was prepared with solid cube and hollow dodecahedra morphologies through in-situ synthesis, and characterized by scanning electron microscopy (SEM), transmission electron microscope (TEM), X-ray diffraction (XRD), Raman, Ultraviolet and visible spectrophotometry (UV/vis), and Fourier transform infrared (FTIR) spectroscopy. In comparison with cubic GO-Cu2O, the absorption and degradation efficiency of the GO-Cu2O dodecahedra (GCD) composite in Methyl orange (MO), Rhodamine B (RhB), and phenol was higher owning to the more active sites for the simultaneous dye and light absorption of hollow structure. The antibacterial effect of the GCD was examined by the flat colony counting method with an excellent bactericidal effect against pathogenic bacteria. The possible mechanism for the preparation of GCD possessing the enhancement of the visible-light photocatalytic and antibacterial efficiencies were also investigated.